Building web-based Filipino language learing tool for heritage learners - Antay, Maria Rosseanna M. (Animo Repository, 2010)
Due to the emigration of millions of Filipinos, the Filipino language is now recognized as one of the major heritage languages. Children of Filipino migrants are exposed to the Filipino language but they did not learn it completely due to emigration and/or formal education in language of country they now live in. Filipino is currently being taught in several States in the US, Guam, Japan, and some of Europe, with enrollees mostly of Philippine descent, or heritage learners. Though there are some teaching resources for Filipino language, these resources are not easily accessible and it is not intended for heritage learners. This paper will discuss salinlahi, a system that was built to cater the needs of the Filipino heritage learners.